The implementation of vpu method to improve the speaking ability of students (a case study of teaching Efl at SMAN 2 Kupang) - Fransiskus Xaverius Ivan Rahas (Politeknik Negeri Bali, 2019)
This study is a classroom action research conducted in the class XII IPA 8 of SMA 2 Kupang in the academic year 2017/2018. This study aims to determine whether the application of the VPU method in learning can improve the ability to speak English in class XII IPA 8 students of SMAN 2 Kupang. The method of data collection in this study was observation, student video recording, and student speaking tests. The data analysis method is quantitative-qualitative descriptive. The results obtained from this study are that the VPU method can improve the speaking skills of students of class XII IPA 8 of SMAN 2 Kupang. This is evident from the results obtained in Cycle I that only 5 students were able to speak English well in class and complete the task of making English conversation videos. In Cycle II, 30 students succeeded in getting speaking score 82.43 and completing the video conversation with the resource person. The data analyzed in this study are a video done by students of class XII IPA 8 and uploaded to social media. The conclusion obtained by this study is that the VPU method can improve students' ability to speak English.